Perancangan E-Sukerti (Surat Keterangan Elektronik) Desa Baturiti Berbasis Web Berbasis Black Box Testing - I Gede Wahyu Sanjaya; Luh Gede Surya Kartika; Putu Kussa Laksmana Utama (Universitas Methodist Indonesia, 2025)
The digital transformation of village administration is a strategic step in enhancing the efficiency and transparency of public services. This study aims to design and develop the E-SUKERTI (Electronic Certificate) system for Baturiti Village, a web-based platform to facilitate the creation and management of electronic certificates. The system development follows a web-based system design approach, with system testing conducted using the Black Box Testing method. Testing was performed with 16 test cases focusing on system functionality to ensure compliance with user requirements. The results indicate that all system features function correctly, achieving a 100% success rate, demonstrating that the system meets its functional requirements. The implementation of E-SUKERTI is expected to improve the speed, accuracy, and transparency of village administrative services for the community.